Biomechanics of sport climbing - Fuss, Franz Konstantin. (2010)
The main goal of the project is to contribute to climbing research through biomechanical analysis of real sport climbing situations rather than relying on laboratory experimental set-ups outwith climbing gyms and facilities. Thus, most of the studies presented in the subsequent chapters were done at different climbing facilities in Singapore. Most studies in the subsequent chapters are carried out with piezoelectric force sensors, attached to climbing holds, for force measurement, and subsequent analysis of mechanical parameters and visualisation of vector diagrams. The evaluation of the mechanical parameters and the interpretation of the results is crucial for the measurement of performance, optimisation of equipment, and improvement of training, as well as for climbing in becoming an Olympic sport.